2022
DOI: 10.5124/jkma.2022.65.11.748
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of the cause of death in Korea in 2019

Abstract: Background: This study aimed to present and analyze the causes of death in the Korean population in 2019.Methods: Based on the Korean Standard Classification of Diseases and Causes of Death and the International Statistical Classification of Diseases and Related Health Problems, 10th revision, cause-of-death data for 2019 from Statistics Korea were examined.Results: There were 295,110 total deaths, a decrease of 3,710 (-1.27%) from 2018. The crude death rate (the number of deaths per 100,000 people) was 574.8,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The data collection and analysis methods were the same as those of the previous study on cause-ofdeath statistics from 2016 study [2] to the 2018-2019 studies [3,4]. Data were obtained from death certificates issued in 2020 for Korean people who had resided in the Republic of Korea [5].…”
Section: Setting Participants Data Source and Measurementmentioning
confidence: 99%
See 3 more Smart Citations
“…The data collection and analysis methods were the same as those of the previous study on cause-ofdeath statistics from 2016 study [2] to the 2018-2019 studies [3,4]. Data were obtained from death certificates issued in 2020 for Korean people who had resided in the Republic of Korea [5].…”
Section: Setting Participants Data Source and Measurementmentioning
confidence: 99%
“…The year 2018 was the first year that life expectancy did not increase since 1970 [3]. However, a followup report showed that life expectancy increased in both 2019 [4] and 2020.…”
Section: ) Mortality Due To Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…This is also true for South Korea, where cardiovascular diseases have consistently been a major cause of death for nearly a decade. An analysis of the trends of the causes of death in Korea from 2009 to 2019 revealed that malignant neoplasms were the most prevalent, followed by cardiovascular diseases [ 2 ]. Notably, when considered as an individual organ disorder, deaths attributable to heart disease were the highest, with a steadily increasing proportion.…”
mentioning
confidence: 99%